Recovery of renal function in a heart transplantation recipient with over 300 days of iatrogenic anuria: A case report. Issue 17 (April 2018) - Peng, Yong-Hua; Yu, Xiao-Min; Yan, Chen; Luo, Lan; Li, Tao-Sheng; Xiao, Jie
Abstract: Rationale: Anuria is a severe symptom indicating severe kidney damage. Patient recovery from prolonged anuria is rarely reported. Patient concerns: A 15-year-old boy received gender- and weight-mismatch heart transplantation (HT) due to dilated cardiomyopathy. He developed severe hypotension, and heart failure 24 hours after surgery, which were relieved by preload reduction treatments. Although, routine examinations did not show any abnormalities in renal function before surgery, anuria occurred 4 days after preload reduction treatments (24-hour urine volume was 23 mL). Diagnosis: The patient was diagnosed with acute kidney injury (AKI). Interventions: He was admitted to continuous renal replacement therapy (CRRT) or hemodialysis. Outcomes: Surprisingly, his urine volume was gradually, and miraculously, restored to more than 1000 mL/24 hours after over 300 days of anuria. Hemodialysis was not needed in the twentieth month after surgery. Moreover, he partially, recovered renal function. Lessons: This case indicates the likelihood of recovery from long-term anuria.